VLSI-SoC: Internet of Things Foundations : 22nd IFIP WG 10.5/IEEE International Conference on Very Large Scale Integration, VLSI-SoC 2014, Playa del Carmen, Mexico, October 6-8, 2014, revised and extended selected papers /: 22nd IFIP WG 10.5/IEEE International Conference on Very Large Scale Integration, VLSI-SoC 2014, Playa del Carmen, Mexico, October 6-8, 2014, revised and extended selected papers. (2015) - Unknown
No abstract available